Phloretamide Protects against Diabetic Kidney Damage and Dysfunction in Diabetic Rats by Attenuating Hyperglycemia and Hyperlipidemia, Suppressing NF-κβ, and Upregulating Nrf2 - Rasha Al-Hussan; Nawal A. Albadr; Ghedeir M. Alshammari; Soheir A. Almasri; Farah Fayez Alfayez; Mohammed Abdo Yahya (MDPI AG, 2024)
Potent hypoglycemic and antioxidant effects were recently reported for the apple-derived phenolic compound phloretamide (PLTM). The renoprotective effects of this compound are yet to be shown. This study aimed to examine the potential of PLTM to prevent diabetic nephropathy in streptozotocin-induced diabetic rats and to examine the possible mechanisms of protection. Non-diabetic and STZ-diabetic male rats were treated orally by gavage with either the vehicle or with PTLM (200 mg/kg; twice/week) for 12 weeks. PTLM significantly increased urine volume and prevented glomerular and tubular damage and vacuolization in STZ-diabetic rats. It also increased creatinine excretion and reduced urinary albumin levels and the renal levels of kidney injury molecule-1 (KIM-1), 8-hydroxy-2'-deoxyguanosine (8-OHdG), neutrophil gelatinase-associated lipocalin (NGAL), and nephrin in the diabetic rats. PTLM also prevented an increase in the nuclear levels of NF-κβ, as well as the total levels of tumor necrosis factor-alpha (TNF-α), interleukin 6 (IL-6), caspase-3, and Bax in the kidneys of diabetic rats. These effects were associated with reduced serum levels of triglycerides, cholesterol, and low-density lipoprotein cholesterol. In both the control and diabetic rats, PTLM significantly reduced fasting plasma glucose and enhanced the renal mRNA and cytoplasmic levels of Nrf2, as well as the levels of Bcl2, superoxide dismutase (SOD), and glutathione (GSH). However, PTLM failed to alter the cytoplasmic levels of keap1 in diabetic rats. In conclusion, PTLM prevents renal damage and dysfunction in STZ-diabetic rats through its hypoglycemic and hypolipidemic activities, as well as through its antioxidant potential, which is mediated by activating the Nrf2/antioxidant axis.